The curious case of Benjamin Button - Kennedy, Kathleen; Marshall, Frank; Chaffin, Cean; Fincher, David; Pitt, Brad; Paramount Pictures; Warner Bros. Pictures (Hollywood, Calif. : Paramount Home Entertainment, 2009)
Daisy Fuller Williams is on her deathbed in a New Orleans hospital the day that Hurricane Katrina hits. At her side is her adult daughter, Caroline. Daisy asks Caroline to read to her aloud from the diary of Daisy's lifelong friend, Benjamin Button. Benjamin's diary recounts his entire extraordinary life. The unusual aspect of his life is that he ages backwards, being born an old man
Title from title screen
Director of photography, Claudio Miranda ; editors, Kirk Baxter, Angus Wall ; music, Alexandre Desplat
Cast: Brad Pitt, Cate Blanchett, Taraji P. Henson, Julia Ormond, Jason Flemyng, Mahershalalhashbaz Ali, Jared Harris, Elias Koteas, Phyllis Somerville, Tilda Swinton
DVD format
Dolby digital
Keywords: Infants -- Diseases -- Louisiana -- New Orleans -- Drama; Human beings -- Aging -- Drama; Man-woman relationships -- Louisiana -- New Orleans -- Drama; Adoptive parents -- Louisiana -- New Orleans -- Drama; Diaries -- Drama